Watermarking in 3D Model Using Dihedral Angle - Laftah , Muna; Jalil , Luma (Iraqi Journal of Science, 2025)
This research is based on a new idea of concealment makes sense depending on the value of the dihedral angle which is the angle between the two planes, concealment began the process of identifying Center of the model and then follow the style of the spider in the process of building his own house in terms of start-point average and then start building the network to walk clockwise and the formation of ring and the transition to the formation of the largest ring, was to follow the same method of concealing data and configure more than one link to the full text is hidden. Method showed very good results in terms of attention to the existence of a change in the picture, because he really has been no change to the original image, the error rate calculation (MSE) and was worth zero results showed good resistance for different types of attack, such as topological, signal attack and geometry so little hidden information destruction did not happen.